Migration, Gender and Care Economy
1 online resource (216 pages)
Keywords: This volume closely analyses women’s role and experiences in migration (internal and international) and its interlinkages with the care economy in their functions as nurses and paid domestic workers as well as unpaid carers. Bringing together case studies from across India and other parts of the world, the essays in the volume capture the characteristics and specificities of female migration in different settings — be it for economic or associational reasons, or as left behind members. The book also looks at gender-specific discriminations and vulnerabilities along with the empowering aspects of migration.This volume will be of great interest to scholars and researchers of migration, gender studies, sociology, and social anthropology, as well as development studies, demography, and economics.